2023
DOI: 10.1093/jisesa/iead004
|View full text |Cite
|
Sign up to set email alerts
|

Odorant-binding Protein 10 From Bradysia odoriphaga (Diptera: Sciaridae) Binds Volatile Host Plant Compounds

Abstract: Bradysia odoriphaga (Diptera: Sciaridae) is a major insect pest of seven plant families including 30 commercial crops in Asia. The long-term use of chemical pesticides leads to problems such as insect resistance, environmental issues, and food contamination. Against this background, a novel pest control method should be developed. In insects, odorant-binding proteins (OBPs) transport odor molecules, including pheromones and plant volatiles, to olfactory receptors. Here, we expressed and characterized the recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…For example, Bradysia odoriphaga shows strong EAG responses to the host plant volatiles methyl allyl disulfide and diallyl disulfide. Fluorescence competitive binding has shown that BodoOBP10 binds strongly to these two host plant volatiles, and RNAi has further indicated that BodoOBP10 is involved in host plant recognition and localization [ 46 , 47 ]. In Sitobion avenae , the OBP SaveOBP9 shows a strong binding force (Ki < 10 μM) with four wheat compounds: tetradecane, octanal, decanal, and hexadecane [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bradysia odoriphaga shows strong EAG responses to the host plant volatiles methyl allyl disulfide and diallyl disulfide. Fluorescence competitive binding has shown that BodoOBP10 binds strongly to these two host plant volatiles, and RNAi has further indicated that BodoOBP10 is involved in host plant recognition and localization [ 46 , 47 ]. In Sitobion avenae , the OBP SaveOBP9 shows a strong binding force (Ki < 10 μM) with four wheat compounds: tetradecane, octanal, decanal, and hexadecane [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A living host of a particular insect can vary greatly based on its life history and feeding guilds, ranging from plants to other animals or humans. Insect OBPs involved in the recognition of host semiochemicals are mainly expressed in the sensillum lymph of the antennae and assist in the adaptation of an insect to their hosts, which has been demonstrated across a diverse range of taxa (131)(132)(133). For example, it was found that An.…”
Section: Host Location and Adaptationmentioning
confidence: 99%
“…Based on the number of conserved cysteine (Cys) residues, insect OBPs can be divided into five subfamilies: classic OBPs (six conserved cysteines), plus-C OBPs (eight conserved cysteines), minus-C OBPs (four conserved cysteines), dimer OBPs (twelve conserved cysteines) and atypical OBPs (nine to ten conserved cysteines) [16,17]. Since the first OBP was found in Antheraea polyphemus [18], more OBPs have been identified based on the transcriptome sequencing technique in recent years [19][20][21][22][23][24][25][26]. Collectively, these studies illustrated that OBPs, which were highly expressed in antennae as well as other body parts (e.g., legs, wings and larval maxilla), showed specific binding affinities with different host plant volatiles, and this phenomenon indicated that OBPs have the function of orientation and host selection at the molecular level.…”
Section: Introductionmentioning
confidence: 99%